2009
DOI: 10.1158/0008-5472.can-08-2491
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan, CD44, and Emmprin Regulate Lactate Efflux and Membrane Localization of Monocarboxylate Transporters in Human Breast Carcinoma Cells

Abstract: Interactions of hyaluronan with CD44 in tumor cells play important cooperative roles in various aspects of malignancy and drug resistance. Emmprin (CD147; basigin)is a cell surface glycoprotein of the immunoglobulin superfamily that is highly up-regulated in malignant cancer cells and stimulates hyaluronan production, as well as several downstream signaling pathways. Emmprin also interacts with various monocarboxylate transporters (MCT). Malignant cancer cells use the glycolytic pathway and require MCTs to eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
146
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(158 citation statements)
references
References 48 publications
7
146
0
2
Order By: Relevance
“…Our flow cytometry results showed much higher expression level of CD147 in CSC-like cells than in NCSCs. Hao et al and Slomiany et al studied CD147 and CD44 expression levels in breast CSCs and found both CD147 and CD44 enriched in CSCs (37)(38)(39). Similar results were observed in our studies.…”
Section: Discussionsupporting
confidence: 92%
“…Our flow cytometry results showed much higher expression level of CD147 in CSC-like cells than in NCSCs. Hao et al and Slomiany et al studied CD147 and CD44 expression levels in breast CSCs and found both CD147 and CD44 enriched in CSCs (37)(38)(39). Similar results were observed in our studies.…”
Section: Discussionsupporting
confidence: 92%
“…MCT1 has been shown to be elevated in a variety of cancers including in MCF7 and MDA-MB-231 human breast cancer cells (30); as shown in Fig. S2, this is also the case for T47D cells.…”
Section: Resultsmentioning
confidence: 63%
“…Though the mechanisms are not fully understood, earlier reports have demonstrated that CD147 interacts with actin (Schlosshauer et al, 1995) and that manipulation of CD147 expression results in reorganization of the actin cytoskeleton (Qian et al, 2008) and formation of actin-rich lamellipodia in Drosophila cells (Curtin et al, 2005); whether these findings are related to the mechanism of invadopodia formation is not known. In addition to its interactions with the actin cytoskeleton, CD147 interacts with several other invadopodia-enriched molecules, such as integrins (Berditchevski et al, 1997) and CD44 (Slomiany et al, 2009), that mediate attachment of ECM components to the cell surface and influence cytoskeleton remodeling. Recent evidence also suggests that CD147 can upregulate various transcription factors leading to multiple downstream signaling events associated with ECM remodeling and invasion .…”
Section: Discussionmentioning
confidence: 99%